The effect of the nano silicon carbide on mechanical properties of aluminium / Rizal Mohamed Noor, Khairul Fauzi Karim and Aznifa Mahyam Zainuddin - Mohamed Noor, Rizal; Karim, Khairul Fauzi; Zainuddin, Aznifa Mahyam (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2007)
This study focuses on nano silicon carbide particulate-reinforced metal-matrix composites processing route using different powder metallurgy techniques; cold press-sintered, hot press-vacuum and effect of milling process. SiC particulates, whose diameters 50~200 nm were choosen for incorporated into Al-3wt% SiC. The microstructures of the samples were investigated by means scanning electron microscopy and correlated to their mechanical properties.